Research Studies on the Creation of an Automated System for Saving Electricity - Abatbayevich, Dauletov Kalniyaz; qizi, Kulmuratova Aliya Janabay (Researchparks Publishing, 2023)
Automation and informatization, smart and digital way are becoming important in all spheres of society. attention, especially in the field of control of automation of electricity, which is economic of the Republic of Uzbekistan development plays a decisive role. Energy-saving design technology for the power of the Republic of Uzbekistan led to a significant increase in industrial efficiency, but also for current electricity energy-saving design technology state of automation and striving to improve imperfect areas, in order to achieve the depth of automation and control technology to accelerate the speed it will be necessary to develop automated control technology. Recently, science and technology in the Republic of Uzbekistan has developed rapidly, more and more automation technologies are applied to production and life activities, which a provides great support for social development and economic development. In the energy system the power of the substation can be intelligently dispatched by automatic control, it is necessary to develop a technology system to reduce manual intervention and increase work efficiency. Using them power transmission automation technology can not only be more orderly and convenient, dispatch and control, but I think it is necessary to significantly improve the efficiency of dispatching power. It is recognized as an important technology for the development of the current energy industry. This the article reveals the features of power transmission automation technology, analyzes the innovative application of power transmission automation.